A gender- and class-sensitive explanatory model for rural women entrepreneurship in Turkey. Issue 2 (24th February 2020) - Kurtege Sefer, Bengu
Abstract : Purpose: The purpose of this paper is to offer a new gender- and class-sensitive framework for research on rural women entrepreneurship by focusing on the women's agricultural cooperatives in Turkey. Although these cooperatives have been promoted as ideal bottom-to-top organizations to integrate women into economy as entrepreneurs, there has been significant decline in their numbers. This paper tackles with this contradictory situation and intends to offer an alternative research framework on the viability of the women's agricultural cooperatives in Turkey. Design/methodology/approach: The paper is built on a critical assessment of the existing literature. It argues that a framework that brings together macro-, meso- and micro-factors will provide a springboard to unfold the gendered processes integral to rural female entrepreneurship in Turkey. Drawing on intersectional theory, the multilayered factors which operate to rural women's (dis)advantages through the cooperatives are unfolded as policymaking, policy implementation and everyday experiences. Findings: For policymakers and implementers, it points out the need for a holistic and integrated understanding of rural female entrepreneurship and for re-formulation of policies at the state level. For rural women, it draws attention to the measures required to be taken at the cooperative level to overcome inequalities. Originality/value: This paper is original in making explicit social, political and economic embeddedness of female entrepreneurship in rural Turkey.